Using of Effective Microorganism Supplementation on Growth Performance of Lao Native Weaned Pigs - KANDEE, Thanousinh; CHANTHAKHOUN, Vongpasith; SINGPHA, Bounlam; BOUYAVONG , Somphan; ONPHACHANH, Xaykham (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Lao native weaned Pig nursery was raised by using mixed feed as a dietary with supplementation effective microorganism (EM) at different levels was aimed to evaluated the growth performance, which were conducted at the experimental farms of the Department of Animal Science, Faculty of Agriculture and Forest Resource at Souphanouvong University during 28 days of nuresing. 12 Lao native weaned pigs at 3.5 kg/pig of average and at 45 days of age were conducted to the complete Complexely Randomized Design (CRD), which consists of three level EM supplementation at 0 ml / 1 kg of dietary (EM0), at 50 ml / 1 kg dietary supplements (EM50) and at 100 ml / 1 kg dietary (EM100). The average daily feed intake (ADFI) was found that significant different (P> 0.05), among treatments, which EM0 = 0.44 kg/day, EM50 = 0.49 kg/day and EM100 = 0.52 kg/day respectively. The average daily growth rate (ADG) of pigs throughout the experiment was found that EM0 = 210 g/day, EM50 = 240 g/day and EM100 = 270 g/day, which found that EM increases was ADG increase significantly different (P< 0.05). The feed conversion ration (FCR) of treatment was found that EM0 = 2.23, EM50 = 1.98 and EM100 = 1.86 respectively and the feed cost per gain was found that EM0 = 7,743.1 Kip / kg, EM50 = 7,189.18 Kip / kg and EM100 = 6,830.0 Kip / kg , no difference significant (P> 0.05). In conclusion that EM supplements in 100 ml / 1 kg of dietary was higher improve to ADFI, ADG, FCR and FCG when comparable tratment that no EM and mysuccession for weaned pig it is possible to use EM supplementation with dietary.